Associations between phenol and paraben exposure and the risk of developing breast cancer in adult women: a cross-sectional study - Yao Xiong; Zhiyu Li; Xiong Xiong; Zixuan Luo; Kaixin Zhong; Jiawei Hu; Shengrong Sun; Chuang Chen (Scientific Reports)
Abstract Increasing evidence suggests that endocrine-disrupting chemicals (EDCs) have adverse effects on breast cancer (BC). The aim of this study was to assess the association between exposure to prevalent EDCs—phenols and parabens—and the risk of developing BC. Data on urinary bisphenol A (BPA), triclosan (TRS), benzophenone-3 (BP3), methyl paraben (MPB), ethyl paraben (EPB), propyl paraben (PPB), and butyl paraben (BUP) were obtained from the 2005–2014 National Health and Nutrition Examination Survey. A total of 4455 subjects were included in this cross-sectional study. The results from the weighted multivariable regression models indicated that exposure to elevated concentrations of TRS increased the risk of developing BC by 2.33 (Q2: 95% CI = 1.45–3.75, p < 0.001) and 1.94 times (Q3: 95% CI = 1.21–3.09, p = 0.006), respectively. The nonlinear association between TRS concentrations and the risk of developing BC was statistically significant (P nonlinear = 0.007), with the restricted cubic splines (RCS) curve exhibiting an inverted U shape. The association between TRS concentrations and the risk of developing BC was more pronounced among overweight individuals (BMI ≥ 25 kg/m2), those aged < 60 years, and white individuals. Weighted quantile sum (WQS) and Bayesian Kernel Machine Regression (BKMR) analysis revealed no significant overall association between mixtures of urinary phenol and paraben metabolites and BC risk. However, TRS exposure was the most influential, with higher TRS concentrations (both continuous and categorical) significantly associated with an increased BC risk, particularly in overweight individuals (BMI ≥ 25 kg/m2), those aged < 60 years, and white individuals.